Substrate Characterization and Outcome of Catheter Ablation of Ventricular Tachycardia in Patients With Nonischemic Cardiomyopathy and Isolated Epicardial Scar. (December 2021) - Liuba, Ioan; Muser, Daniele; Chahal, Anwar; Tschabrunn, Cory; Santangeli, Pasquale; Kuo, Ling; Frankel, David S.; Callans, David J.; Garcia, Fermin; Supple, Gregory E.; Schaller, Robert D.; Dixit, Sanjay; et al.
Abstract : Background: The substrate for ventricular tachycardia (VT) in left ventricular (LV) nonischemic cardiomyopathy may be epicardial. We assessed the prevalence, location, endocardial electrograms, and VT ablation outcomes in LV nonischemic cardiomyopathy with isolated epicardial substrate. Methods: Forty-seven of 531 (9%) patients with LV nonischemic cardiomyopathy and VT demonstrated normal endocardial (>1.5 mV)/abnormal epicardial bipolar low-voltage area (LVA, <1.0 mV and signal abnormality). Abnormal endocardial unipolar LVA (⩽8.3 mV) and endocardial bipolar split electrograms and predictors of ablation success were assessed. Results: Epicardial bipolar LVA (27.3 cm 2 [interquartile range, 15.8–50.0]) localized to basal (40), mid (8), and apical (3) LV with basal inferolateral LV most common (28/47, 60%). Of 44 endocardial maps available, 40 (91%) had endocardial unipolar LVA (24.5 cm 2 [interquartile range, 9.4–68.5]) and 29 (67%) had characteristic normal amplitude endocardial split electrograms opposite the epicardial LVA. At mean of 34 months, the VT-free survival was 55% after one and 72% after multiple procedures. Greater endocardial unipolar LVA than epicardial bipolar LVA (hazard ratio, 10.66 [CI, 2.63–43.12], P =0.001) and number of inducible VTs (hazard ratio, 1.96 [CI, 1.27–3.00], P =0.002) were associated with VT recurrence. Conclusions: In patients with LV nonischemic cardiomyopathy and VT, the substrate may be confined to epicardial and commonly basal inferolateral. LV endocardial unipolar LVA and normal amplitude bipolar split electrograms identify epicardial LVA. Ablation targeting epicardial VT and substrate achieves good long-term VT-free survival. Greater endocardial unipolar than epicardial bipolar LVA and more inducible VTs predict VT recurrence. Abstract : Supplemental Digital Content is available in the text.